The effects of oil price shocks on the Iranian economy - Mohammad Reza Farzanegan; Gunther Markwardt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
The Iranian economy is highly vulnerable to oil price fluctuations. This paper analyzes the dynamic relationship between oil price shocks and major macroeconomic variables in Iran by applying a VAR approach. The study points out the asymmetric effects of oil price shocks; for instance, positive as well as negative oil price shocks significantly increase inflation. We find a strong positive relationship between positive oil price changes and industrial output growth. Unexpectedly, we can only identify a marginal impact of oil price fluctuations on real government expenditures. Furthermore, we observe the Dutch Disease syndrome through significant real effective exchange rate appreciation.
Keywords: E32; E37; Q32; 330; macroeconomic uctuations; oil price shocks; developing economies; Iran; VAR modelling; Mineralölpreisschock; Makroökonomischer Einfluss; VAR-Modell; Iran